Utilization of flaxseed powder in controlling lipid oxidation and quality deterioration of fried goat meat patties - Raheel Suleman; Hira Choudhary; Ivan A. Garcia-Galicia; Tariq Ismail; Muhammad Qamar; Muhammad Aftab Zahoor; Sabahat Zulfiqar; Isam A. Mohamed Ahmed; Moneera O. Aljobair (Cogent Food & Agriculture)
Flaxseed is a limited and unexplored natural source for food product stabilization and quality enhancement. Our aim was to utilize flaxseed powder (FP) at different concentrations (2%, 4%, 6% and 8%) and a control (no FP) to investigate its effect on the quality and oxidative stability of cooked goat meat patties. Our results showed that the variation in antioxidants was significant (p < .05) among treatments owing to the presence of antioxidants at each concentration. DPPH (2,2-diphenyl-1-picrylhydrazyl) concentration varied between 71% and 75%. The total phenolic content varied significantly in the range of 180–274.9 mg GAE/g. The ferric reducing antioxidant power activity also varied significantly from 47.9 to 57.3 mg/g. Minimum lipid oxidation was found in goat meat patties with a higher percentage of FP (8%). The range of lipid oxidation varied from 487.1 to 148.2 mg/kg to 8%, showing that flaxseed is a useful source of natural antioxidants and can be used as a natural ancillary to synthetic antioxidants BHA and BHT to decrease their levels in products. Future studies could investigate the usage of lower FP concentrations or certain ingredients like antioxidants or PUFAs to better maximize its advantages in goat meat preservation to support these findings.